Identification of Delay Factors from Mecca's Construction Experts Perspective - Al-Emad, Nashwan Hamid; Nagapan, Sasitharan (International Journal of Sustainable Construction Engineering and Technology, 2015)
Delay in construction project is a common phenomenon in construction industry project where there are numerous studies on this issue that identified the factors causing the delay. This paper presents a study on identifying significant delay factors encountered by construction practitioners in Mecca city. A total of 81 delay factors were identified from seven research articles on construction delay study conducted in several parts of Saudi Arabia. These factors were included in the questionnaire form where this questionnaire was distributed amongst the construction experts who involved in the current construction projects in Mecca. The survey was carried out by interviewing 28 selected experts, who are from consultant, contractors and project management’s parties.  The collected data were analyzed by using Average Index method for each factor and these factors were ranked based on the index to determine its significance to the delay. The result found that the most six significant factors are Changes in design documents, Low productivity level of labour, Shortage of manpower, Difficulties in financing project by contractor, Poor contract management, and Unqualified workforce. The results of this research are helpful to the construction community in avoiding any potential delay for their future construction projects in order to achieve successful construction projects.